Diagnostic Significance of Neutrophil to Lymphocyte Ratio in Recurrent Aphthous Stomatitis: A Systematic Review and Meta-Analysis - Mohammad Javad Rahimi; Fariba Mirakhori; Rebecca Zelmanovich; Christina Sedaros; Brandon Lucke-Wold; Gersham Rainone; Arshin Ghaedi; Shokoufeh Khanzadeh (Mattioli1885, 2024)
Introduction: Recurrent aphthous stomatitis (RAS) is a prevalent ulcerative condition affecting oral mucosa. Objectives: A systematic review and meta-analysis was performed to compare the level of neutrophil to lymphocyte ratio (NLR) between individuals with RAS and those who are healthy. Methods: A systematic search for relevant publications before June 21, 2022, was conducted using Web of Science, PubMed, and Scopus. The results were presented as the standardized mean difference (SMD) with a 95% confidence interval (CI), and a random-effects model was used to calculate pooled effects due to the presence of significant heterogeneity. Quality assessment was performed using the Newcastle-Ottawa scale. Results: Overall, 13 article with were included in the analysis. NLR was higher among patients with RAS compared to healthy controls (SMD = 0.50, 95% CI = -0.20 to 0.79, P = 0.001, I2 = 91.5%). In the subgroup analysis based on the study design, it was found that retrospective studies showed higher levels of NLR in patients with RAS compared to healthy controls (SMD = 0.62, 95% CI= 0.16 to 1.08, P < 0.01), but these results were not applied to prospective studies (SMD = 0.35, 95% CI = -0.03 to 0.74, P < 0.07). Conclusion: Elevated neutrophil to lymphocyte ratio revealed crosstalk between systematic inflammation and RAS.